Empowering underprivileged students: A collaborative education enrichment initiative by UiTM and PKAYIS. - Wan Mohd, Wan Nor Hafidzah; Suhadak, Nurulzulaiha; Ahmad, Haryati; Mahmood, Che’ Khalilah; Zainon, Saunah (Journal of Islamic, Social, Economics and Development, 2025)
Pertubuhan Kebajikan Anak-Anak Yatim Islam Daerah Segamat (PKAYIS) was established as an effort to address the needs of orphans in the Segamat District, Johor, Malaysia. Among others, this welfare organization aims to provide shelter and support for academic learning for these orphans who are also usually underprivileged students. However, PKAYIS faces the challenge of high tuition fees hindering the orphaned children under their care from attending paid supplementary classes or external tuitions. Recognizing the importance of academic support, UiTM Johor has joined forces with PKAYIS to resolve the matter. UiTM academicians contribute their expertise in English, Mathematics, and Science subjects, serving as tutors and coordinators for supplementary classes or tutoring programs. The tutors consist of lecturers from the Faculty of Computer and Mathematical Sciences, Academy of Language Studies, and Faculty of Accountancy. Meanwhile, the coordinators also come from various colleges and faculties within UiTM Johor, and they diligently follow the set schedule and provide necessary class resources, including contributing food and beverages for attending students. This collaboration between UiTM Johor and PKAYIS extends beyond community service; it serves as a UiTM consultancy project with significant impact on the local community, particularly in the education sector. UiTM fully supports the Malaysian Ministry of Education's efforts to make the education system more inclusive. This initiative aligns with UiTM's commitment to maintain a high-quality education system, nurture individual potential, and contribute to national aspirations.